Fiber-enriched wheat flour precooked using extrusion processing: rheological, nutritional and sensory properties - Gajula, Hyma (Kansas State University, 2007)
Foods with high fiber can reduce calorie uptake and provide health benefits related to chronic ailments like obesity, diabetes, cancer and cardiovascular disease. However, inclusion of fiber diminishes the final product quality and consumer acceptability of cereal products. The overall objective of this project was to produce fiber-enriched, pre-cooked wheat flours using extrusion processing in order to enhance their nutritional value, while maintaining functional and sensory properties in baked products such as cookies and tortillas. In the first part of this study, extrusion processing was utilized to pre-cook wheat flours substituted with 0, 10, 20 and 30 % wheat bran in order to enhance their rheological properties and functionality with regards to cookies and tortillas. Two extrusion conditions, low-temperature-low-shear (LTLS) and high-temperature-high-shear (HTHS) were studied for pre-cooking the flours. Results showed that for all flours, as % bran increased, RVA peak viscosity (PV), and mixograph peak time (PTM) and peak height (PH) decreased. At all bran levels, PV and PH were significantly lower for pre-cooked flours as compared to uncooked. As the percent bran increased, the quality of cookies (weight and spread factor) and tortillas (specific volume, rollability and extensibility) deteriorated for both uncooked and pre-cooked wheat flours. In the second part of this study, effect of extrusion pre-cooking on the dietary fiber profile of wheat flour substituted with 0, 10, 20 and 30 % wheat bran was evaluated. Pre-cooking by extrusion significantly increased SDF in flours (by 22 to 59 %), although in most cases it also led to a significant decrease in TDF. Cookies and tortillas, produced from uncooked and pre-cooked flours with 0 and 20% substituted bran, were evaluated for consumer acceptability using a 9-point hedonic scale. Organoleptic properties of cookies from uncooked flour did not change significantly with increase in bran substitution from 0 to 20%. However, consumer ratings for tortillas did decrease slightly but significantly with increase in bran level. To summarize, pre-cooking of the flours using extrusion did not improve the sensory properties of cookies and tortillas, although the products were still found acceptable by consumers and also contained higher soluble fiber.
Keywords: Extrusion; pre-cooking; wheat bran; functional and reheological properties; cookies; tortillas; Agriculture, Food Science and Technology (0359)